Network structure and metropolitan mobility - Pavithra Parthasarathi (Journal of Transport and Land Use)
This research aims to develop quantitative measures that capture various aspects of the underlying network structure, using aggregate level travel data from fifty metropolitan areas across the US. The influence of these measures on system performance is then tested using statistical regression models. The results corroborate that the quantitative measures of network structure affect the system performance. The results from this analysis can be used to develop network design guidelines that can be used to address current transportation problems.